Implementasi Pendidikan Karakter dalam Mata Pelajaran Ilmu Pengetahuan Sosial - Raudah Devi Ekasari; Liza Savira; Erni Musnatiwi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Social studies subject is a learning process for humans that aims to make students have positive behavior and interesting skills. Character education is a component of social science studies. From this research, the aim is to determine the supporting and inhibiting factors in the implementation of character education at SD Krajan 1 Magetan on social studies subjects. Thus this study contributes to education regarding how character education in elementary schools experienced by students in social studies learning. The results of this study are the implementation of character education has gone according to plan, because it is supported by teacher factors, character-based school management and community support. There are several obstacles such as the problem of attitude assessment and environmental factors, so the solution to overcome the problem is to create an assessment format and use of monitoring cameras in each hallway and class. The research method needed is to use qualitative research, so that the data collection technique is through interviews and observation.